2015
DOI: 10.1055/s-0040-1703935
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding body and organ donation amongst the population of an urban city in India

Abstract: Purpose : Bodies for purpose of dissection and organs for transplantation surgeries are needed for education of medical students and treatment of cases of end-stage organ failure. However deceased organ donation rate in India is very dismal. In the present study the authors assess the knowledge and attitude of the people living in an urban city in India towards organ and body donation. Materials/Methods : A questionnaire was distributed amongst all willing patients and their relatives attending the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…More than 90% of the study population knew that eyes and kidneys can be donated. Similar findings were reported in the study done in South Kerala [10], but in the study done in Pune [18] knowledge about kidney donation was found to be very less compared to the present study. 66.2% of study population of Saleem T et al [19] and 95.4% of participants of Soubhanneyaz A et al [20] were aware about kidney donation programs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More than 90% of the study population knew that eyes and kidneys can be donated. Similar findings were reported in the study done in South Kerala [10], but in the study done in Pune [18] knowledge about kidney donation was found to be very less compared to the present study. 66.2% of study population of Saleem T et al [19] and 95.4% of participants of Soubhanneyaz A et al [20] were aware about kidney donation programs.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the respondents 64.2% in the present study had good attitude and thought that organ donation should be promoted but only 47.8% showed willingness to donate organs. This finding is almost similar to the studies done in South Kerala [10] and Pune [18]; but much less than that reported in Chennai [4] and Mangalore [11]. More proportion of subjects in the present study were not selective in their desire to donate organs which was found to be similar to findings in the study conducted by Ramadurga UY and Gupta A [21].…”
Section: Discussionsupporting
confidence: 90%
“…Similar observation were made by other such Indian studies, people were generally aware about eye donation followed by kidney donation. [11][12][13] The ex- tensive mass media campaigns using celebrities in recent years might be the reason behind such awareness.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar state of poor awareness was observed in studies conducted in Maharashtra. 12,13 However, the studies that have made efforts to understand the issue in India are very few and these are largely limited to urban area. Any comparative studies for better understanding of urban-rural difference are ever rarer.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in studies done in Kanchipuram (86%), Ahmedabad (86%), and Maharashtra (78%). [ 5 18 19 ] Studies done in Kerala showed that almost all the participants have heard about organ donation. Higher awareness regarding the term organ donation among our study population can be attributed to the higher educational status of the participants.…”
Section: Discussionmentioning
confidence: 99%